Nanoemulsion Improves the Antifungal Activity of Allylic Thiocyanates against Yeasts and Filamentous Pathogenic Fungi. Issue 41 (8th November 2018) - Dalla Lana, Daiane F.; Giuliani, Laura M.; Reolon, Jéssica B.; Lopes, William; Vainstein, Marilene H.; Danielli, Letícia J.; Bergamo, Vanessa Z.; Pippi, Bruna; Apel, Miriam A.; Teixeira, Mário L.; de Oliveira, Luis F. S.; Machado, Michel M.; et al.
Abstract: We report the antifungal and antichemotactic activities of a series of allylic thiocyanates with low toxicity. We also show improved antifungal activity of the most promising compound when used in a nanoemulsion (NE). The 4‐chlorophenyl‐substituted allylic thiocyanate (compound11 ) exhibited a broad spectrum of antifungal activity and showed antichemotactic effects with 100% reduction in leucocyte migration. Minimal inhibitory concentrations ranged from 25 to 50 μg mL −1, and the mechanism of action was related to complexation with fungal ergosterol. The NE containing compound11 enhanced the antifungal activity approximately 64‐fold for dermatophytes and 4‐fold for Candida spp.. Compound11 was not mutagenic and did not cause cell death or significant haemoloysis, although it exhibited mild dose‐dependent DNA damage. It was not an irritant for chorioallantoic membrane of fertile white eggs and exhibited 100% inhibition of fungal growth in an in vivo model of dermatophytosis. Our data indicate that allylic thiocyanates are very promising for the antifungal potential in nanostructured systems, with associated anti‐inflammatory effect. Abstract : We report allylic thiocyanates as antifungal agents of broad spectrum, with associated anti‐inflammatory effect. A nanoemulsion with the most promising compound (4‐chlorophenyl substituted allylic thiocyanate) improved the antifungal activity. The mechanism of action was related to complexation with fungal ergosterol, with low toxicity to human leukocytes and absence of irritability to the chorioallantoic membrane. Finally, the most promising compound exhibited 100% inhibition of fungal growth in an in vivo model of dermatophytosis.